EMOTIONAL ANALYSIS OF CHILDREN IN CLASS I PRIMARY SCHOOL - J. Sunarti; Iip Istirahayu; Slamat Fitriyadi (STKIP Singkawang, 2017)
This study aims to describe the emotional dynamics of first grade students at the beginning of the lesson and at the end of the lesson of one elementary school in Singkawang City and to analyse the factors causing the emotions of the first grade students at the beginning of the lesson and at the end of the lesson on one elementary school in Singkawang City. This type of research is qualitative research. Sources of data used are class I and Teacher homeroom I. Data collection techniques that researchers use is participatory observation in the process of learning in the classroom at the beginning and end of the lesson. Interview techniques in the form of structured interviews used to obtain information as complete as possible. Data collection techniques with documents in the form of writing and photos. Data Collecting Instrument used in this research are observation sheet, interview questionnaire and activity photo. The results explain the emotional dynamics in the first grade students of Brother Singkawang Elementary School at the beginning of the lesson is 100% happy. At the end of the hour 18% happy, 18% sad, and 63% angry. Factors causing emotions happy at the beginning of the lesson because it can meet friends, play and learn together. As for sad and angry emotions are not visible. At the end of the lesson there are happy emotions caused by content to play, full because they have eaten and ready to learn again and can answer teacher questions. The sad emotion at the end of the lesson is caused by still want to play, sick, hot weather, tired or tired and fighting. Furthermore, feelings of anger caused by a friend's fight and bullied, hot weather, angry due to the teacher warned and hyperactive.